The Andersen–Newman Behavioral Model of Health Service Use as a conceptual basis for understanding patient behavior within the patient–physician dyad: The influence of trust on adherence to statins in older people living with HIV and cardiovascular disease - Petrovic, Kimberly; Blank, Thomas O (Cogent psychology, 2015)
The observation that “(d)rugs don’t work in patients who don’t take them” seems obvious; however, for older people living with HIV and cardiovascular disease (CVD), the potential for taking large numbers of medications on a regular basis may present as an overwhelming task, particularly as HIV and CVD progress and worsen over time. The extent to which older people living with HIV and CVD follow medication schedules for the treatment of these chronic health conditions is not understood well, and myriad questions exist with regard to medication adherence and older people living with HIV and CVD. For instance, do older people living with HIV and CVD take all medications as prescribed? Does this group prioritize which medications to take, perhaps demonstrating a preference for taking antiretroviral medications for the treatment of HIV as opposed to statins for the treatment of CVD? In the process of answering these and other questions, recognizing the individual and his or her attitudes and behaviors within the context of the dyadic relationship shared between patient and physician is paramount. Developing a more thorough understanding of this dyadic relationship allows for a better grasp of the context within which medication adherence occurs for older people living with HIV and CVD. That said, because of the ability to lend itself to an understanding of human behavior, human development, and psychology, the Andersen and Newman Behavioral Model of Health Service Use provides a worthwhile conceptual basis for beginning to answer these questions. © 2015 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.
Keywords: CVD; HIV and AIDS; adherence; dept.fye; dyadic relationship; older adults; trust